Effectiveness of a steel ring-frame for the seismic strengthening of masonry walls with new openings - Oña Vera, Mónica.Y. (2021)
The creation of new openings in masonry walls is a frequent intervention in existing buildings. Depending on their size and position, these interventions may cause a significant decrease of the wall’s original in-plane strength and stiffness, thus compromising the building seismic resistance. Therefore, in masonry buildings, strengthening techniques may be required to (i) restore as much as possible the loss of stiffness and strength, (ii) be reversible and (iii) respect the compatibility between materials, particularly in the case of historical buildings. In an attempt to comply with these requirements, engineering practitioners often introduce very stiff steel profiles forming a ring-frame inside the opening for fully restoring the stiffness and resistance without substantially increasing the building's weight. However, the effectiveness of this technique is typically quantified using linear elastic analysis and a simple sum of the flexural and shear stiffness of the masonry panels and the steel ring-frame. The present work aims to improve the knowledge and better understanding of the effectiveness of this traditional steel ring-frame technique, through experimental and numerical methods. The experimental program was designed to provide a full assessment of the effects of introducing a new door opening in brick masonry walls, from the cutting process to the application of in-plane cyclic lateral deformations. The steel ring-frame was designed using numerical tools and consisted of four profiles welded together and tied to the surrounding masonry wall by means of steel dowels dry-driven into calibrated holes of the brick. Results show that the steel ring-frame system restores the original solid wall’s in-plane strength and ductility, but not the lateral stiffness, despite the use of large steel profiles.